Overseas state outsiders as new sources of patient capital: Government policies to welcome Sovereign Wealth Fund investment in France and Germany - Thatcher, M; Vlandas, T (Oxford University Press, 2017)
Strong debates in the varieties of capitalism literature as to whether financial liberalization and internationalization undermine ‘insider’ corporate governance systems based on patient capital in coordinated and state-led market economies have focused on ‘impatient’ overseas private capital. However, cross-border state investment has also grown. We examine government policies towards a prominent type of state investment—equity purchases by sovereign wealth funds (SWFs). We argue that policymakers in ‘insider’ corporate governance systems can see such investment as an attractive international source of patient capital to offset declines in traditional sources of patient capital. We compare Germany and France and show that policymakers actively welcome SWF investment. Policy is driven by coalitions of ‘insiders’ of the managements of large industrial firms and governments who seek passive patient capital and beneficial relationships with overseas investors. Thus, financial liberalization and internationalization can allow new sources of patient capital through overseas state investors.